2021
DOI: 10.4081/monaldi.2021.2065
|View full text |Cite
|
Sign up to set email alerts
|

Loss of engagement in controlling chronic anticoagulation therapy during Covid-19 stringency measures. A single center experience of disproportioned increase of stuck mechanical valves

Abstract: Stuck valve is a very rare and severe complication that occurs in mechanical valve replacement patients with ineffective anticoagulation. However, with COVID-19 restriction measures, it became challenging to regularly assess INR to make sure it falls within the target therapeutic range to prevent this complication. We present a series of 10 patients who either underwent transthoracic echocardiography for a suspected stuck valve or were seen at the outpatient valve clinic with the residual consequences of a stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The most frequent risk factors contributing to PVT include inadequate anticoagulation, AF, recent infection, and plasma fibrinogen level, as reported by Bezanjani et al Furthermore, with regards to inadequate anticoagulation, it has been recently recognized that public policy-related COVID-19 restriction measures have posed a challenge for patients and physicians to regularly assess patients’ INR levels and ensure effective anticoagulation; Vriz et al found that the incidence of stuck prosthetic valves has significantly increased amid these restrictions [ 24 ]. While we acknowledge that COVID-19 restriction measures themselves may have had an influence on PVT incidence during the COVID-19 pandemic, it is important to note that none of the cases included in this review noted significant non-adherence to anticoagulation medication nor INR check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent risk factors contributing to PVT include inadequate anticoagulation, AF, recent infection, and plasma fibrinogen level, as reported by Bezanjani et al Furthermore, with regards to inadequate anticoagulation, it has been recently recognized that public policy-related COVID-19 restriction measures have posed a challenge for patients and physicians to regularly assess patients’ INR levels and ensure effective anticoagulation; Vriz et al found that the incidence of stuck prosthetic valves has significantly increased amid these restrictions [ 24 ]. While we acknowledge that COVID-19 restriction measures themselves may have had an influence on PVT incidence during the COVID-19 pandemic, it is important to note that none of the cases included in this review noted significant non-adherence to anticoagulation medication nor INR check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the COVID-19 pandemic has made it difficult for patients to visit anticoagulation clinics to obtain AMSs (Gong et al, 2020;Zhang, 2020). Previous studies have shown a significant increase in adverse events of warfarin treatment during COVID-19 stringency measures (Vriz et al, 2021). Therefore, measures should be taken to improve the anticoagulation quality of patients during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%